КЛИНИКО-ФУНКЦИОНАЛЬНЫЕ СОСТАВЛЯЮЩИЕ БРОНХОЛЕГОЧНОГО СИНДРОМА ПРИ ДИСПЛАЗИИ СОЕДИНИТЕЛЬНОЙ ТКАНИ - М. В. Вершинина; Г. И. Нечаева; Л. М. Гринберг; С. Е. Говорова; А. А. Хоменя; Н. В. Багишева (SINAPS LLC, 2015)
To study the respiratory symptomatology in patients with connective tissue dysplasia (CTD) were surveyed 305 young people. Clinical and functional components of bronchopulmonary syndrome in CTD were identified through a comprehensive examination, including the use of standardized questionnaires and scales, and functional methods.